Laser Ignition System for Internal Combustion Engine (International Journal of Engineering and Computer Science, 2017)
Laser ignition is considered to be one of the most promising future ignition concepts for internal combustion engines. It combines the legally required reduction of pollutant emissions and higher engine efficiencies. In technical appliances such as internal combustion engines, reliable ignition is necessary for adequate system performance. Economic as well as environmental constraints demand a further reduction in the fuel consumption and the exhaust emissions of motor vehicles. At the moment, direct injected fuel engines show the highest potential in reducing fuel consumption and exhaust emissions. Study of ignition of combustion processes is of great importance. In most cases, a well-defined ignition location and ignition time is crucial for an IC engine. Spark plugs are well suited for such tasks but suffer from disadvantages, like erosion of electrodes or restricted positioning possibilities. Thermodynamic requirements of a high compression ratio and a high power density are fulfilled well by laser ignition. Laser ignition can enhance the combustion process and minimize pollutant formation. At present the laser ignition plug is very expensive and commercially not yet available.